2009
DOI: 10.1080/15391523.2009.10782542
|View full text |Cite
|
Sign up to set email alerts
|

Using Video Editing to Cultivate Novice Teachers’ Practice

Abstract: %is article reports research concerning the effective use of video editing to he4 cultivate novice teachers' reflective practice. Ihe study reported here is part of is larger body of research on video-enhanced teacher reflection. For this study, we useda qualitative research design to examine two guided reflection activities for two groups of novice teachers. lhe first group debriefed with a teacher educator immediately after teaching their lesson. Bey hter wrote about critical incidents that occurred during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 21 publications
5
39
0
12
Order By: Relevance
“…De acuerdo a este modelo analítico se recogió información sobre tres tipos de apoyo a la reflexión: una herramienta técnica que apoya la reflexión, una herramienta técnica con una guía predefinida que ayudó a promover la reflexión, y una herramienta técnica con la interacción humana (pares o profesores apoyaron la reflexión). Varios investigadores en el campo de la formación de profesores (Calandra, Brantley-Dias, Lee y Fox, 2009;Crawford, O'Reilly, Luttrell, 2012;Stockero, 2008;Yaffe, 2010) han informado que la observación de videos de la propia enseñanza beneficia el aprendizaje de los maestros. Los videos se usan para situar el aprendizaje, desarrollar hábitos de reflexión (Stockero, 2008), y mejorar la autoconciencia (Yaffe, 2010).…”
Section: Procedimientos De Búsqueda De Literaturaunclassified
See 3 more Smart Citations
“…De acuerdo a este modelo analítico se recogió información sobre tres tipos de apoyo a la reflexión: una herramienta técnica que apoya la reflexión, una herramienta técnica con una guía predefinida que ayudó a promover la reflexión, y una herramienta técnica con la interacción humana (pares o profesores apoyaron la reflexión). Varios investigadores en el campo de la formación de profesores (Calandra, Brantley-Dias, Lee y Fox, 2009;Crawford, O'Reilly, Luttrell, 2012;Stockero, 2008;Yaffe, 2010) han informado que la observación de videos de la propia enseñanza beneficia el aprendizaje de los maestros. Los videos se usan para situar el aprendizaje, desarrollar hábitos de reflexión (Stockero, 2008), y mejorar la autoconciencia (Yaffe, 2010).…”
Section: Procedimientos De Búsqueda De Literaturaunclassified
“…Los videos se usan para situar el aprendizaje, desarrollar hábitos de reflexión (Stockero, 2008), y mejorar la autoconciencia (Yaffe, 2010). Trabajar con videos da a los estudiantes maestros la oportunidad de analizar los detalles de sus lecciones (Calandra et al, 2009). Además, los datos de audio y vídeo pueden ser complementos útiles para el aprendizaje porque proporcionan un punto de vista y representaciones detalladas (Bannink y van Dam, 2007).…”
Section: Procedimientos De Búsqueda De Literaturaunclassified
See 2 more Smart Citations
“…Research reported several benefits on teachers' reflective ability regarding interpersonal relationships and classroom management after the implementation of video in their classroom (Bryan & Recesso, 2006;Calandra, Brantley-Dias, Lee & Fox, 2009). Generally speaking, synchronous video communication is integral part of all mobile devices, e-learning platforms, and social networks sites.…”
Section: Introductionmentioning
confidence: 99%